Prospective study of the Iliac Bicrest Pubic Angle through the 3D reconstruction of the bone pelvis and the correlation with giant incisional hernia - MENDES,CARLOS JOSÉ LAZZARINI (2022)
ABSTRACT Objective: to describe and measure the Bicrista Iliaca Pubo Angle (APBCI) as a new anthropometric parameter. Correlate the measurement with patients with giant incisional hernia (HIG), in the midline of the anterior abdominal wall (AAW). Methods: measurement of APBCI, through 3D reconstruction from computed tomography (CT). Measurements performed by two observers, R and C, in 246 women and 60 men, normal adults, in order to obtain the APBCI measurement and its correlation in patients with HIG of the AAW. Results: after sample calculations, the measurement of APBCI in men: 92.5+6.3º to 93.8+6.7º; in women: 90+6.7° to 94.3+6.8° [p-value 0.337(R)/0.628(C)]. The mean age was 57.9+15.9 years (22 to 91 years). Female gender 57+15.7 years (22 to 91 years) and male 61.7+16.5 years (23 to 89 years) p=0.067. As for the distribution of the ranges from 5 to 5 degrees, there is no difference in the distribution of the angle [p-value 0.455(R)/0.672(C)]. The correlation between age and angle showed that the higher the age, the higher the APBCI. There was no variability between angle measurements: 0.97 (95% CI 0.97; 0.98). In men with HIG, the average is between 108.3+5.37º (102.92º to 113.67º), and in women, 107.8+6.64 (101.16º to 114.44º). Conclusion: the study allowed us to conclude that HIG is not just an isolated AAW defect. Determines skeletal changes, as the APBCI is influenced by the distance of the iliac crests.